Medicinal Plants Used for Treating Mild Covid-19 Symptoms Among Thai Karen and Hmong - Phumthum, Methee; Nguanchoo, Varangrat; Balslev, Henrik (Frontiers in Pharmacology, 2021)
The COVID-19 pandemic is causing many severe problems globally, and it is not known for how long it will last. The only hope we have for dealing with the problem is to produce sufficient vaccines. However, the current demand for vaccines greatly exceeds the supply, and many people will suffer from the disease for still some time. Moreover, the period for immunity obtained by the vaccines remains unknown, and we cannot predict how long the world will suffer the COVID-19 infections. Therefore, there will be a continued demand for treatments of its symptoms. An alternative solution for providing such treatment is the use of traditional medicinal plants. To document medicinal plants used by Hmong and Karen in Thailand to treat mild symptoms of COVID-19. Traditional knowledge about ethnomedicinal plants used by Hmong and Karen in Thailand for treating mild symptoms listed by WHO as associated with COVID 19, was collected in field interviews and extracted from the literature. Results: We identified 491 plant species used medicinally by both ethnic groups to treat fever, cough, diarrhea, muscle pain and ache, rash, headache, sore throat, and conjunctivitis. Of the 491 species, 60 were mentioned at least five times in the literature or in our field data. Of these 60 species, we propose the most commonly used ones for treatments of mild COVID-19 symptoms. Ten of these most commonly mentioned species were used for treatments of fever, nine for treatment of cough, four for treatments of diarrhea, two for treatment of rash, and a single species was used to treat muscle pain and headache. This study suggests alternative treatments for mild symptoms of COVID-19 with medicinal plants that are traditionally used by the ethnic minority groups of the Hmong and Karen in Thailand. Although COVID-19 is a new disease, its mild symptoms are shared with many other diseases. Traditional knowledge on medicinal plants used by the Thai Karen and Hmong could help in the treatments of these symptoms associated with COVID-19. Many of the proposed plants were used abundantly by both ethnic groups, and other scientific evidence supports their efficacy in such treatments.